Pengaruh Resiliensi dan Status Rantau Terhadap College Student Subjective Well-Being pada Mahasiswa - Ivonne Qumairi; Asri Mutiara Putri; Prida Harkina (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2021)
Abstract: College students subjective well-being is an evaluation of someone’s life. That is, the extent of their meaningful assessments and affective reactions indicate that their life is desirable and going well. Several factors affected college students subjective well-being, such as resilience and demographics (overseas status). The research aims to describe the effect of resilience and overseas status on college students subjective well-being. The type of this research is quantitative research. The data collection method used demographic data on student status, college student subjective well-being questionnaire and resilience through a google form. The subjects in this research were college students in Bandar Lampung, amounting to 451 respondents using the accidental sampling technique. In this study, data analysis used multiple regression techniques. Based on the result of statistical tests, a significance value of .000 is .000 .05. These show that resilience and student status simultaneously affect college students' subjective well-being with a correlation value of .640. in addition, resilience partially affect college student subjective well-being.Furthermore, these show that the higher the resilience, the higher the subjective well-being of the college student. However, partially overseas status does not affect college students subjective well-being. Overseas and non-overseas student status cannot affect college students subjective well-being.Keywords: college student subjective well-being;resilience;overseas status;college student Abstrak:College student subjective well-being merupakan evaluasi seseorang tentang kehidupannya, yaitu sejauh mana penilaian bermakna dan reaksi afektif mereka menunjukkan bahwa hidup mereka diinginkan dan berjalan dengan baik. Beberapa faktor yang mempengaruhi college student subjective well-being antara lain resiliensi dan demografi (status rantau). Penelitian ini bertujuan untuk memaparkan pengaruh resiliensi dan status Rantau terhadap college student subjective well-being pada mahasiswa. Jenis Penelitian Ini Merupakan Penelitian Kuantitatif. Metode Pengumpulan data menggunakan data demografi status mahasiswa, college student subjective well-being questionnaire dan kuesioner resiliensi melalui media google form. Subjek dalam penelitian ini yakni mahasiswa di Bandar Lampung yang berjumlah 451 responden dengan menggunakan teknik accidental sampling. Dalam Penelitian Ini Analisis data menggunakan teknik regresi berganda. Berdasarkan Hasil uji statistik, diperoleh nilai signifikansi sebesar .000 yang dimana .000 .05. Hal ini menunjukkan bahwa resiliensi dan status mahasiswa secara bersama-sama (simultan) mempengaruhi college student subjective well-being dengan nilai korelasi sebesar .640. Selain itu, resiliensi secara parsial mempengaruhi college student subjective well-being pada mahasiswa. Hal tersebut menunjukkan semakin tinggi resiliensi maka semakin tinggi pula college student subjective well-being pada mahasiswa. Namun, secara parsial status rantau tidak mempengaruhi college student subjective well-being pada mahasiswa. status mahasiswa rantau dan bukan rantau tidak dapat mempengaruhi college student subjective well-being pada mahasiswa.Kata Kunci: college student subjective well-being; resiliensi; status rantau; mahasiswa